Development and single‐particle analysis of hybrid extracellular vesicles fused with liposomes using viral fusogenic proteins - Raga Ishikawa; Shosuke Yoshida; Shin‐ichi Sawada; Yoshihiro Sasaki; Kazunari Akiyoshi (FEBS Open Bio, 2022)
Extracellular vesicles (EVs) have potential biomedical applications, particularly as a means of transport for therapeutic agents. There is a need for rapid and efficient EV‐liposome membrane fusion that maintains the integrity of hybrid EVs. We recently described Sf9 insect cell‐derived EVs on which functional membrane proteins were presented using a baculovirus‐expression system. Here, we developed hybrid EVs by membrane fusion of small liposomes and EVs equipped with baculoviral fusogenic proteins. Single‐particle analysis of EV‐liposome complexes revealed controlled introduction of liposome components into EVs. Our findings and methodology will support further applications of EV engineering in biomedicine.